Enhanced EPR directed and Imaging guided Photothermal Therapy using Vitamin E Modified Toco-Photoxil. Issue 1 (December 2018) - Chauhan, Deepak; Bukhari, Amirali; Ravichandran, Gayathri; Gupta, Ramkrishn; George, Liya; Poojari, Radhika; Ingle, Aravind; Rengan, Aravind; Shanavas, Asifkhan; Srivastava, Rohit; De, Abhijit
Abstract Herein we report synthesis, characterization and preclinical applications of a novel hybrid nanomaterial Toco-Photoxil developed using vitamin E modified gold coated poly (lactic-co-glycolic acid) nanoshells incorporating Pgp inhibitor d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as a highly inert and disintegrable photothermal therapy (PTT) agent. Toco-Photoxil is highly biocompatible, physiologically stable PTT material with an average diameter of 130 nm that shows good passive accumulation (2.3% ID) in solid tumors when delivered systemically. In comparison to its surface modified counterparts such as IR780-Toco-Photoxil, FA-Toco-Photoxil or FA-IR780-Toco-Photoxil accumulation are merely ~0.3% ID, ~0.025% ID and ~0.005% ID in folate receptor (FR) negative and positive tumor model. Further, Toco-Photoxil variants are prepared by tuning the material absorbance either at 750 nm (narrow) or 915 nm (broad) to study optimal therapeutic efficacy in terms of peak broadness and nanomaterial's concentration. Our findings suggest that Toco-Photoxil tuned at 750 nm absorbance is more efficient (P = 0.0097) in preclinical setting. Toco-Photoxil shows complete passiveness in critical biocompatibility test and reasonable body clearance. High tumor specific accumulation from systemic circulation, strong photothermal conversion and a very safe material property in body physiology makes Toco-Photoxil a superior and powerful PTT agent, which may pave its way for fast track clinical trial in future.